THE RELATIONSHIP BETWEEN SPIRITUAL WELL-BEING AND RESILIENCE IN STUDENTS FROM FATHERLESS BACKGROUNDS - Napouling, Debby; Yunithree Suparman, Meiske (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to examine the relationship between spiritual well-being and resilience among university students with a fatherless background. The study uses a quantitative correlational approach with the Spiritual Well-Being Scale (SWBS) to measure spiritual well-being and the Connor-Davidson Resilience Scale (CD-RISC) to assess resilience. The sample consisted of 268 students aged 18–24 years, spanning from the 1st to the 7th semester. Data were collected using questionnaires measuring spiritual well-being, resilience, and the fatherless condition experienced by the respondents. The results show a strong positive relationship between spiritual well-being and resilience among fatherless students. Most respondents (90.3%) showed moderate levels of resilience, while 9.7% exhibited high resilience. Spiritual well-being was generally moderate among respondents. This study emphasizes the importance of strengthening spiritual well-being as a source of strength in building resilience among students from fatherless families. The findings also have implications for the development of psychological intervention programs that integrate spiritual aspects to enhance students' mental toughness. ABSTRAK Penelitian ini bertujuan untuk mengkaji hubungan antara kesejahteraan spiritual dan ketahanan diri di kalangan mahasiswa yang memiliki latar belakang tanpa ayah. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan Skala Kesejahteraan Spiritual (SWBS) untuk mengukur kesejahteraan spiritual dan Skala Ketahanan Connor-Davidson (CD-RISC) untuk menilai ketahanan diri. Sampel penelitian terdiri dari 268 mahasiswa berusia 18–24 tahun, yang tersebar dari semester 1 hingga semester 7. Data dikumpulkan menggunakan kuesioner yang mengukur kesejahteraan spiritual, ketahanan diri, dan kondisi tanpa ayah yang dialami oleh responden. Hasil penelitian menunjukkan hubungan positif yang kuat antara kesejahteraan spiritual dan ketahanan diri di kalangan mahasiswa tanpa ayah. Sebagian besar responden (90,3%) menunjukkan tingkat ketahanan diri yang moderat, sementara 9,7% menunjukkan ketahanan diri yang tinggi. Kesejahteraan spiritual secara umum berada pada tingkat moderat di kalangan responden. Penelitian ini menekankan pentingnya penguatan kesejahteraan spiritual sebagai sumber kekuatan dalam membangun ketahanan diri di kalangan mahasiswa dari keluarga tanpa ayah. Temuan ini juga memiliki implikasi untuk pengembangan program intervensi psikologis yang mengintegrasikan aspek spiritual untuk meningkatkan ketangguhan mental mahasiswa.